2(m-6)=-18

Simple and best practice solution for 2(m-6)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-6)=-18 equation:


Simplifying
2(m + -6) = -18

Reorder the terms:
2(-6 + m) = -18
(-6 * 2 + m * 2) = -18
(-12 + 2m) = -18

Solving
-12 + 2m = -18

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2m = -18 + 12

Combine like terms: -12 + 12 = 0
0 + 2m = -18 + 12
2m = -18 + 12

Combine like terms: -18 + 12 = -6
2m = -6

Divide each side by '2'.
m = -3

Simplifying
m = -3

See similar equations:

| -26.17-(+18.52)= | | P=2(68)+2(145) | | -12(x-1)=4(x+13) | | 7=3w+4w | | 4x+2=-16 | | -15-49= | | s+(s+.89)=92.99 | | 2x+21=6x-9 | | 4(16+13)-2(3-4)=x-4 | | 4.1f+9.22=-12.10+2.9+8.15 | | 9x^2-9=31 | | 4(16+3)-2(3-4)=x-4 | | 2x+30=90 | | 6x+(5x-20)=90 | | p+p+33+3p-37=696 | | 12x+3=x+8 | | 10x-6ax+3=5a+3ax | | -2+x/-4=-14 | | z-8z=9z-8-z | | 9x+6y=-9 | | 250=50-3+b | | 6x+8-9(x+1)=4x+3 | | -(2x+1)-(3+4X)+5X=3x-8.9 | | -x/7=1/16 | | z-7z=6z-5-z | | 6x+5x+20=90 | | 15=x/5+7 | | x+.02x=22.73 | | y=b+50x | | x+.02x=22.23 | | f(x)=-0.022x^4-0.457x^3-2.492x^2-5.279x+87.419 | | Y=0x+7 |

Equations solver categories